2012
DOI: 10.1134/s0869591111060026
|View full text |Cite
|
Sign up to set email alerts
|

Indian MORB-type mantle beneath the Kuril Island arc: Isotopic investigation of the mafic lavas of Kunashir Island

Abstract: New data on the Hf, Pb, and Nd isotopes of the mafic rocks of various ages from Kunashir Island were used to address the nature of the sub arc mantle of the southern segment of the Kuril island arc. At least since Late Cenozoic, its isotopic characteristics have been the MORB type mantle of the Indian Ocean. Its boundary with the mantle reservoir of the Pacific MORB type coincided probably with the Kuril-Kam chatka Trench.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Geochemistry, Geophysics, Geosystems 10.1002/2015GC005911 et al, 2014M. Ban et al, JTABS project, unpublished data, 2015], Kurile [Martynov et al, 2012], and Japan Sea floor basalts [Hirahara et al, 2015] (Figure 6b). Additionally, DSDP/ODP sediment core sample data from southern Tonga [Pearce et al, 2007] and Izu [Chauvel et al, 2009] and basalt data from the Shatsky Rise [Heydolph et al, 2014] are plotted in Figure 6c.…”
Section: Nd-hf Isotopesmentioning
confidence: 99%
See 2 more Smart Citations
“…Geochemistry, Geophysics, Geosystems 10.1002/2015GC005911 et al, 2014M. Ban et al, JTABS project, unpublished data, 2015], Kurile [Martynov et al, 2012], and Japan Sea floor basalts [Hirahara et al, 2015] (Figure 6b). Additionally, DSDP/ODP sediment core sample data from southern Tonga [Pearce et al, 2007] and Izu [Chauvel et al, 2009] and basalt data from the Shatsky Rise [Heydolph et al, 2014] are plotted in Figure 6c.…”
Section: Nd-hf Isotopesmentioning
confidence: 99%
“…[] reported that the radiogenic Pb was largely from the altered oceanic crust (AOC) of the Pacific Plate, and they proposed that the Pacific Plate younger than ∼125 Ma was generated from the previously subducted Izanagi‐Pacific Ridge (IPR) [ Nakanishi et al ., ], which produced MORBs of Indian mantle provenance (Indian‐type MORB or AOC) as young as 125 Ma. This proposal is contrary to previous models that relied on Pb‐Sr‐Nd isotopic geochemistry of the arc lavas to determine the provenance of the Indian mantle wedge [ Flower et al ., ; Hickey‐Vargas et al ., ; Kimura and Yoshida , ; Kimura and Nakajima , ; Kimura et al ., ; Martynov et al ., ; Pearce et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible geochemical effects of subductionrelated processes on the composition of primary mantle material of suprasubduction zones have been discussed in detail in previous studies (Martynov et al, 2007(Martynov et al, , 2012Martynov and Kimura, 2009). These effects are reflected, in particular, in marked enrichment of the suprasubduction mantle wedge in LREE, LILE, Pb, and Sr.…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, low-temperature aqueous fluids are less capable of mobilizing LREE, and depletion in LREE of island-arc rocks indicates the involvement of a subduction-related component in magma genesis (Martynov et al, 2012). Enrichment in Cs, Rb, Ba, U, Pb, and Sr and depletion in Nb, Ta, and LREE are typical of suprasubduction zone lavas generated with the involvement of a low-temperature aqueous fluid (Martynov and Kimura, 2009).…”
Section: Discussionmentioning
confidence: 99%